Major revision version 11.0 of the European AIDS Clinical Society Guidelines 2021. Issue 8 (25th March 2022) - Ryom, Lene; De Miguel, Rosa; Cotter, Aoife Grace; Podlekareva, Daria; Beguelin, Charles; Waalewijn, Hylke; Arribas, Josè R; Mallon, Patrick W. G.; Marzolini, Catia; Kirk, Ole; Bamford, Alasdair; Rauch, Andri; et al.
Abstract: Background: The European AIDS Clinical Society (EACS) Guidelines were revised in 2021 for the 17th time with updates on all aspects of HIV care. Key points of the Guidelines update: Version 11.0 of the Guidelines recommend six first‐line treatment options for antiretroviral treatment (ART)‐naïve adults: tenofovir‐based backbone plus an unboosted integrase inhibitor or plus doravirine; abacavir/lamivudine plus dolutegravir; or dual therapy with lamivudine or emtricitabine plus dolutegravir. Recommendations on preferred and alternative first‐line combinations from birth to adolescence were included in the new paediatric section made with Penta. Long‐acting cabotegravir plus rilpivirine was included as a switch option and, along with fostemsavir, was added to all drug–drug interaction (DDI) tables. Four new DDI tables for anti‐tuberculosis drugs, anxiolytics, hormone replacement therapy and COVID‐19 therapies were introduced, as well as guidance on screening and management of anxiety disorders, transgender health, sexual health for women and menopause. The sections on frailty, obesity and cancer were expanded, and recommendations for the management of people with diabetes and cardiovascular disease risk were revised extensively. Treatment of recently acquired hepatitis C is recommended with ongoing risk behaviour to reduce transmission. Bulevirtide was included as a treatment option for the hepatitis Delta virus. Drug‐resistant tuberculosis guidance was adjusted in accordance with the 2020 World Health Organization recommendations. Finally, there is new guidance on COVID‐19 management with a focus on continuance of HIV care. Conclusions: In 2021, the EACS Guidelines were updated extensively and broadened to include new sections. The recommendations are available as a free app, in interactive web format and as an online pdf.